Neuroendocrine Associations Underlying the Persistent Therapeutic Effects of Classic Serotonergic Psychedelics - Schindler, Emmanuelle A. D.; Wallace, Ryan M.; Sloshower, Jordan A.; D’Souza, Deepak C. (Frontiers in Pharmacology, 2018)
Recent reports on the effects of psychedelic-assisted therapies for mood disorders and addiction, as well as the effects of psychedelics in the treatment of cluster headache, have demonstrated promising therapeutic results. In addition, the beneficial effects appear to persist well after limited exposure to the drugs, making them particularly appealing as treatments for chronic neuropsychiatric and headache disorders. Understanding the basis of the long-lasting effects, however, will be critical for the continued use and development of this drug class. Several mechanisms, including biological and psychological ones, have been suggested to explain the long-lasting effects of psychedelics. Actions on the neuroendocrine system are some such mechanisms that warrant further investigation in the study of persisting psychedelic effects. In this report, we review certain structural and functional neuroendocrinological pathologies associated with neuropsychiatric disorders and cluster headache. We then review the effects that psychedelic drugs have on those systems and provide preliminary support for potential long-term effects. The circadian biology of cluster headache is of particular relevance in this area. We also discuss methodologic considerations for future investigations of neuroendocrine system involvement in the therapeutic benefits of psychedelic drugs.